Logistics business transformation for sustainability: Assessing the role of the lead sustainability service provider (6pl) - Tim Gruchmann; Ani Melkonyan; Klaus Krumme (Logistics, 2018)
Societal, economic and ecological prosperity will be highly affected in the next decades due to socio-demographic developments and climate change. The design of more sustainable logistics business types can address such challenges to build more resilient supply chains. Therefore, the discussion with regard to transformational potentials of logistics businesses provides valuable information to shape business strategies according to future sustainability requirements. Within the framework of this paper, a mixed-methods approach has been applied to explore and analyze drivers and barriers for sustainability transformations of logistics service providers (LSPs) and to evaluate related business strategies with optimization and simulation methods in a concrete regional context. So far, LSPs' main obstacles are competitive pressure, focal firm orientation, and dependence on other supply chain members, while supply chain collaboration and integration, as well as the integration of sharing economy solutions and new digital technologies, have been identified as promising for sustainability transitions. Accordingly, this paper suggests a roadmap for the logistics sector while defining retention strategies such as growth, replication, mimicry, and mergence to meet future societal and environmental requirements. By doing so, this study contributes to theory by constructing the Lead Sustainability Service Provider (6PL) business model (arche)type and its role in societal transitions.
Keywords: 650; business model classification; business transformation; strategy development; sustainable logistics; sustainable supply chain management